Safety and Efficacy of Overdilation of 10 mm Viatorr Transjugular Intrahepatic Portosystemic Shunt Stents Using 12 mm Balloons - Muhammad Mohid Tahir; Trevor K. Lewis; Aamir Ali; Michael Hsu; Jeffrey L. Weinstein; Muneeb Ahmed; Ammar Sarwar (The Arab Journal of Interventional Radiology)
Objective The aim of this study was to evaluate overdilation of 10-mm standard and 8–10 mm controlled-expansion Viatorr stents to 12 mm during transjugular intrahepatic portosystemic shunt (TIPS) placement when insufficient reduction (<50%) in portosystemic gradient (PSG) is achieved with standard 10 mm dilation.